Possible Improvement of Oocyte Supply by the use of Aged Mice and Different Gonadotrophins - Myungook Lee; Jong Il Ahn; Hyosook Kwun; Dong Woo Ko; Jiyeon Ahn; Jeong Mook Lim (The Korean Society of Animal Reproduction and Biotechnology, 2018)
This study was conducted to examine the influences of two human chorion gonadotrophins (hCGs) being injected into young or aged (45- to 65-week old) outbred (ICR) mice on developmental capacity of oocytes retrieved. in vitro-culture and parthenogenetic activation of oocytes retrieved were employed for the assessment. Superovulation was determined as being induced when more than 25 oocytes were retrieved. No aged mice were superovulated, while in contrast, 67-100% were superovulated in the 6- to 8-week-old (young) mice. In the aged, hCG injection yielded better retrieval (5 vs. 13 to 14.8 oocytes/mouse). Overall, no significant difference between two hCGs was detected but between the young and aged, significant differences in maturational arrest (0% vs. 39% MI arrest and 46% vs. 15% degeneration) and developmental capacity (24% vs. 46% 8-cell embryo development) were detected. In conclusion, hCG injection contributes to increasing oocyte retrieval from aged outbred mice, but the kinds of gonadotrophin influenced the efficiency of hyperstimulation induction in specific ages.